HUBUNGAN KEKUATAN OTOT TUNGKAI DAN DAYA LEDAK DENGAN KEMAMPUAN HASIL LOMPAT JAUH PADA SISWA MA AL-BARKAH SUMBERJAYA - Fentiana; Abrar; Basman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to examine the relationship between leg muscle strength and explosive power with long jump performance among students of MA Al-Barkah Sumberjaya. A quantitative correlational design was used, involving 27 students selected through purposive sampling. Leg muscle strength was measured using a leg dynamometer, explosive power using the standing broad jump test, and long jump performance using a standard long jump test. Data were analyzed using Pearson product moment correlation and multiple linear regression. The results showed a positive and significant correlation between leg muscle strength and long jump performance (r = 0.439; p = 0.022), and a stronger positive and significant correlation between explosive power and long jump performance (r = 0.695; p = 0.000). Simultaneously, both variables were significantly related to long jump performance (R = 0.695; R² = 0.483; F = 11.232; p = 0.000), contributing 48.3% to the variance in long jump results, with explosive power being the more dominant predictor. These findings suggest that physical education teachers should emphasize explosive power training, particularly plyometric exercises, to improve students' long jump performance.